Histološke značilnosti kosti pri nekaterih presnovnih kostnih boleznih - Legan, Mateja (Medicinski razgledi, 2004)
The author presents the bone biopsy: indications for the procedure, laboratorytreatment of the sample and bioptic histological pictures of major metabolic bone diseases. Bone biopsy retains the most important role in nephrology for the determination of variants of renal bone disease, a consideration which is important for therapeutic decisions. In endocrinology, it is important for the diagnosis of (mostly) occult osteomalacia and hereditary disorders and to clarify diagnostic biases.
Keywords: Bone Diseases, Metabolic; Hiperparatiroidizem; Kost, bolezni presnovne; Pathology; Ledvična osteodistrofija; Osteoporosis; Osteomalacia; Osteomalacija; Osteoporoza; Hyperparathyroidism; Renal Osteodystrophy; Biopsija; Biopsy; kosti; diagnostika; presnovne bolezni; histologija